Papieskie apele do Polski w sprawie pomocy dla Ziemi Świętej (XII-XIV w.) - Kowalska, Anna (Acta Universitatis Lodziensis. Folia Historica, 2000)
The papal appeals reached Poland in all important matters connected with events or plans related to the Holy Land. The first call for taking part in the crusade to Jerusalem was dated from 1095. The next appeals went before the second, third, fifth and bloodless crusades. In the second half of the 13-th and in the first half of the 14-th centuries the papacy called on the Faithful to participate in the intended crusades. They were not usually realized. The popes told the priests to preach in order to encourage Poles to fight not only in Palestine but also elsewhere. They had the same privileges those ones as setting out to Jerusalem. They might fight with Slaves from Polabie, tribes from Prussia and Tatars. They could also help to keep and later to regain the Latin Empire. They might fight against some people: Bolesław the Bald and the antipope Robert. The papacy often demanded money from those one, who wanted to free themselves from the vows of taking part in crusades. There were other ways of helping the Holy Land. The popes imposed tithes and ordered to put money into money-boxes in churches. They claimed sums, which were bequeathed to Palestine. Indirect responses to the papal appeals for help the Holy Land, with money and deed, were donations for the orders originating from there. It was a form of buying oneself out of taking part in the crusades, on the other hand that money was sent to the East and might be used as means in fighting against Saracens. Such fundations were found in Silesia, Great Poland and West Pomerania. The mentions in the historical sources are the arguments that papal call not only were known in medieval Poland but also that the society responed to them.